Utilizing Reflective Writing in Reading Proficiency Class (Proceedings of English Linguistics and Literature, 2022)
Reflection has long been thought to be a viable technique for dealing with issues in various fields. This paper aims to investigate the difficulties in reading tasks, and the strategies used by the students shown in reflective writing in reading proficiency class. A qualitative method using narrative inquiry was used in this study. More specifically, the participants of the study consisted of 14 postgraduate students from a university in Jakarta. They were required to make reflections after they finished doing reading tasks that had different levels of the Common European Framework of Reference (CEFR), namely B2 and C1. Four reflective writings focussing on the B1 CEFR standard from four different participants were taken purposively as they contain a complete explanation. It can be revealed that there are some difficulties in reading tasks, such as unrelated theme, identical keywords, and a lack of lexical knowledge. Besides, there are strategies used by the students, such as guessing the unfamiliar vocabulary, finding keywords, and understanding the context. From the findings, students and educators can plan better for students’ higher level of reading proficiency.